2019
DOI: 10.2340/00015555-3349
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Matrix Metalloproteinases-1, -9, Transient Receptor Potential Vanilloid Type 1, and CD117 in Granulomatous Rosacea Compared with Non-granulomatous Rosacea

Abstract: Fig. 1. (A, B) Patients with granulomatous rosacea (GR) had periocular lesions and showed an asymmetrical distribution. (C, D) Patients with nongranulomatous rosacea (NGR) spared the periocular area and showed a symmetrical distribution. Permission is given to publish these photos. For complete details, see Fig. S1 1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As the only variant, GR differs from non‐granulomatous rosacea (NGR) in clinical presentations and histopathological findings, and has a unique pattern of inflammatory cell infiltration. Granuloma requires the recruitment of immune cells like lymphocytes and histiocytes, 6 but the mechanisms remain debatable 7 . Initially, the mycobacterium tuberculosis infection was thought to be the cause of GR, 8 but in 1949, Snapps found that GR was not induced by tuberculid and had no association with tuberculosis 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the only variant, GR differs from non‐granulomatous rosacea (NGR) in clinical presentations and histopathological findings, and has a unique pattern of inflammatory cell infiltration. Granuloma requires the recruitment of immune cells like lymphocytes and histiocytes, 6 but the mechanisms remain debatable 7 . Initially, the mycobacterium tuberculosis infection was thought to be the cause of GR, 8 but in 1949, Snapps found that GR was not induced by tuberculid and had no association with tuberculosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Granuloma requires the recruitment of immune cells like lymphocytes and histiocytes, 6 but the mechanisms remain debatable. 7 Initially, the mycobacterium tuberculosis infection was thought to be the cause of GR, 8 but in 1949, Snapps found that GR was not induced by tuberculid and had no association with tuberculosis. 9 Subsequently, demodex was suspected to be an important pathogenic cause of GR, which however has not been proven yet in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…These MMPs belong to the gelatinase family and cooperatively participate in the degradation of gelatin and collagen type I [ 28 ]. Few studies have assessed the expression of MMP-9 in facial skin samples of rosacea patients [ 21 , 29 ]; nonetheless, several studies have explored its levels in other bodily fluids such as tears and serum [ 30 , 31 ]. Interestingly, results from those studies indicate that rosacea has the potential to modify the concentrations of MMP-9 in these bodily fluids at a distance, hinting at a broader and “systemic” impact of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Skin biopsies are usually unnecessary; nevertheless, they might still be crucial for differential diagnosis with other similar yet pernicious conditions such as angiosarcoma [ 29 ]. Therefore, it is necessary to have certainty in the early diagnosis of rosacea and complement it with the detection of specific biomarkers of this disease [ 30 ]. In this study, we hypothesize that rosacea influences the GCF levels of MMP-2 and -9 regardless of periodontal status and thus can be used as a novel diagnostic biomarker for rosacea.…”
Section: Introductionmentioning
confidence: 99%